A 35‐year‐old mystery solved: a facile synthetic route and structural confirmation of tetrachlorobis(diethyl ether)tungsten(IV). Issue 4 (12th March 2021) - Shaw, Thomas E.; Sattelberger, Alfred P.; Jurca, Titel
Abstract : The existence of the bis(diethyl ether) adduct of WCl4 has been confirmed. Room‐temperature X‐ray diffraction studies of the adduct reveal two coordinated diethyl ether molecules and establish the identity of the complex as trans ‐WCl4 (Et2 O)2 . Abstract : The true identity of the diethyl ether adduct of tungsten(IV) chloride, WCl4 (Et2 O) x, has been in doubt since 1985. Initially postulated as the bis‐adduct, WCl4 (Et2 O)2, questions arose when elemental analyses were more in line with a mono‐ether adduct, viz. WCl4 (Et2 O). It was proposed that this was due to the thermal instability of the bis‐adduct. Here, we report the room‐temperature X‐ray crystal structure and Hirshfeld surface characteristics of trans ‐tetrachloridobis(diethyl ether)tungsten(IV), trans ‐WCl4 (Et2 O)2 or trans ‐[WCl4 (C4 H10 O)2 ]. The compound crystallizes, with half of the molecule in the asymmetric unit, in the centrosymmetric space group P 21 / n . The W—O distance is 2.070 (2) Å, while the W—Cl distances are 2.3586 (10) and 2.3554 (10) Å.